Ethical issues in counselling: a systematic review of literature - Arokianathan, Nathynie; Zakaria, Noor Syamilah; Subarimaniam, Neerushah (Innovare Academics Sciences, 2020)
Ethical issues is a norm in the counselling field. Counsellors have codes of ethics to guide them in their practice. However, the decision is based on their critical thinking and choice to do what they think is right. This systematic review explores the ethical issues and supervisors and supervisees’ opinions regarding ethical concerns. Culture of distinct countries is also taken into account. SAGE electronic database was used to search for related journals and the search resulted in 10 journals. This review presents journals as a result from inclusion and exclusion criteria. The ethical issues such as client referral, confidentiality, in-home or outpatient counselling, gifts receiving, and various setting and countries are tabulated systematically. The counsellors refer to United States (US) ACA (American Counselling Association) Codes of Ethics when encountering ethical issues. However, this systematic review depicts that findings are distinct in terms of individual perception, culture, and norms of the counselling field.